THE INTERNET REVOLUTION - Montes Farro, Eduardo Alberto (2010)
When Alvin Toffler foreshadowed the Third Wave civilization, and n ted the importance of information. Well, time has proved right, and you can accept that we are witnessing a new era. The basic tool for this fact is called the Internet, whose features are being implemented in many activities, and not just develop. Taking the example of management, which involves active participation from all areas of the organization, where information is an essential resource, using Internet services, you can see how it exercises its influence, identifying a powerful impact on all life of society. In this environment, the accounting professional, a generator of information, have a significant participation and contribution to knowledge and business management.